Unfulfilled need for contraception among women with unmet need but with the intention to use contraception in Rakai, Uganda: a longitudinal study - Tom Lutalo (BMC Women's Health, 2018)
Abstract Background Longitudinal data from a rural Ugandan cohort was used to estimate rates of unfulfilled need for contraception, defined as having unmet need and intent to use contraception at baseline but having an unintended pregnancy or with persistent unmet need for contraception at follow up. Methods Between 2002 and 2009 (5 survey rounds), a total of 2610 sexually active non-pregnant women with unmet need for contraception at the start of an inter-survey period were asked whether they intended to use any method of contraception until they desired a child. Modified Poisson multivariate regression was used to estimate unadjusted and adjusted prevalence ratios (PR) and 95% CI of unfulfilled need for contraception. Results The proportion of women with unmet need at the start of an interval who intended to use contraception significantly increased from 61 to 69.1% (p < 0.05). However the majority of women who said they intended to use contraception had unfulfilled need for contraception at the subsequent survey (64.8 to 56.8%). In the adjusted analysis, significant predictors of unfulfilled need for contraception included age 40–49 years (PR = 1.34; 95% CI 1.04–1.74) and those with unknown HIV status (PR = 1.16; 95% CI 1.06–1.26). Conclusions There is a significant discrepancy between women’s intent to use contraception (> 60%) and subsequent initiation of use (< 30%) with many having unintended pregnancies which might explain the persistent high fertility in Uganda. Future research needs to address unfulfilled need for contraception among women at risk of unintended pregnancies.